Túnel de vento de camada limite atmosférica : metodologia de projeto - Silva Junior, Moacyr Fauth da (2006)
The present work has as its main subject the design and calculation of two atmosferic boundary layer wind tunnels. It is with their possible assembly at the University of Passo Fundo, to perform researches in the field of Wind´s Engineering. The work is strutured around four chapters: Introduction, where the theme and objectives are explained; Review, where the state-of-the-art is present; Projects, where calculations and design are showed; Conclusions and sugestions for future works